(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2021)
Since its independence, India has made enormous strides in inclusive growth, cementing its status as one of the biggest economies. Despite the fact that India’s economic power is expanding, the country is still ranked among the bottom five in terms of public health expenditure. The Indian healthcare industry is still struggling from underinvestment and bad administration, which has resulted in significant disparities in basic health-care delivery. While India’s health spending has increased little in recent years, the government intends to raise it. India’s current health expenditure per capita is near to 72.834, implying that the country has spent fewer public funds on health than most advanced nations.